Analisis Dampak Kabut Asap Karhutla Terhadap Gangguan Kesehatan Mental - Putra Mulia; Nofrizal; Wan Nishfa Dewi (STIKes Payung Negeri Pekanbaru, 2021)
Forest and land fires in Indonesia on 2019, has caused haze disaster. Pekanbaru City becomes one of the affected regions. The purpose of the study is to analyze the effect of pollutant exposure towards physical and mental health problems of the people. The analysis of physical health effect due to pollutant exposure uses Spearman’s rho correlation. The analysis of mental health effect due to pollutant exposure is analyzed descriptively. Concentration of particulate matter with diameters less than or equal to 10 micrometer reached 374 point (very unhealthy). Spearman’s rho correlation result obtained between AQI and asthma (p = 0,000), acute respiratory infections (p = 0,000), pneumonia (p = 0,005), conjunctivitis (p = 0,000), dermatitis (p = 0,001), and diarrhea (p = 0,002), and it can be concluded that there is a significant relationship betwwen unhealthy air quality with physical health problems. There was no increase in cases of acute stress, anxiety, and PTSD during the haze disaster period